Assessing Proactive Investigation Techniques Against Corruption: A Comparative Study of Indonesia, the United States, Hong Kong, and Singapore - Khristiya Lutfiasandhi; Ayu Dian Ningtias; Dewi Ajeng Sintia Putri (Jurnal Independent, 2026)
The Indonesian Criminal Procedure Code (KUHAP) does not formally recognize the term Operasi Tangkap Tangan (OTT) or "Sting Operation." The regulation concerning a red-handed arrest is strictly provided under Article 1 point 19 of the KUHAP. In executing an OTT, the Corruption Eradication Commission (KPK) primarily utilizes two techniques: wiretapping (surveillance) and entrapment (sting operations). While the KPK Law explicitly grants the authority to conduct wiretapping, it does not provide detailed procedural regulations. Furthermore, the concept of entrapment is not formally recognized within various Indonesian anti-corruption statutes.However, from a legal perspective, the OTTs conducted by the KPK do not violate criminal procedural law. This is because, at the time of the arrest, the suspect is found in possession of objects strongly suspected to have been used to commit the crime, indicating their role as the perpetrator, an accomplice, or an accessory to the offense. Furthermore, these operations do not infringe upon the presumption of innocence or fundamental human rights, as the KPK carries out the OTT in accordance with the procedures established Indonesia Law.